О влиянии космофизических факторов на работу фотоэлемента с медным катодом - Таращук, В.П. (Известия Крымской астрофизической обсерватории, 2007)
Registration velocity of the gas-filled photocell with the copper cathode is systematically higher at the days of the positive polarity of interplanetary magnetic field as compared to the days of negative polarity. Registration velocity has a tendency to show the 27-day repeatability, which is associated with changing of the integral index of solar activity F10. These dependencies are stipulated, probably, by the influence of the over low frequency background electromagnetic field on the output of electrons of photocell cathode.